LONGEVIDADE DE RESTAURAÇÕES ATRAUMÁTICAS EM PRÉ- ESCOLARES REALIZADAS COM DIFERENTES TIPOS DE CIMENTO DE IONÔMEROS DE VIDRO - Cançado, Naiana Mello (2016)
This clinical trial main objective was to evaluate the survival of atraumatic restorative treatment restorations (ARTs) in 3-5 years old children using four different types of glass ionomer cements (GIC). After sample size calculation an amount of 301 ARTs were placed in 110 children at their school, according to the following treatment groups: GC Gold Label - GC (n=72), Maxxion R – FGM (n=76), Ketac Molar Easymix – 3M ESPE (n=77) and Vitrofil LC – DFL (n=76). The ARTs were evaluated clinically at 3, 6, 9 and 12 months after placement, by one trained and blinded examiner, according to the ART evaluation criteria. The collected data were analyzed using Kaplan-Meier survival test and Log-rank test setting the significance level at 5%. After 12 months, the success rates of the ARTs were 68.4%, regardless the type of cavity or GIC brand used. When the type of the cavity was considered, single surface cavities achieved success rates of 78,4%, 76,3%, 67,3% and 75% for GC Gold Label, Ketac Molar Easymix, Maxxion R and Vitrofil, respectively. Multiple surface cavities, the success rates were 77,3% for GC Gold Label, 57,5% for Ketac Molar Easymix, 52,6% for Maxxion R and 50% for Vitrofil. No statistical differences were detected among GIC brands (p>0.05). However, there was significant differences when comparing the types of cavities. The multiple surface cavities present a greater chance to fail, irrespective of the GIC used (p=0.05). After 12 months, the mean survival period was 9.9 months (95% CI: 9.5-10.3), regardless the restorative material used. No interferences of the independent variable age and ICDAS scores were detected. It’s concluded that the survival of ART restorations was not affected by the brand of the GIC used and that single surface cavities showed higher survival rates than multiple surface ones, regardless the GIC used.